Fondasi Etis dan Strategi Epistemik dalam Pembelajaran Islam: Analisis Isi terhadap Kitab al-Ilm karya Muhammad bin Shalih Al-Utsaimin - Muklas Muklas; Aang Mahyani (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This qualitative library research examines the ethical foundations and learning strategies for seekers of knowledge as articulated by Muhammad bin Ṣāliḥ Al-Utsaimin in Kitab al-Ilm. Using content analysis, the study systematically codes thematic units related to intention, discipline, reverence for scholars, epistemic verification, and pedagogical method. The findings reveal twelve interconnected ethical principles that function not merely as moral guidance but as an integrated epistemic framework. These include sincerity of intention, commitment to acting upon knowledge, respect for scholarly authority, patience in learning, intellectual humility, and verification of information. Complementing these ethical foundations are practical strategies such as prioritizing foundational knowledge, structured study routines, memorization and revision (murāja’ah), guided mentorship (mulāzamah), and selective academic companionship. The study argues that Al-Utsaimin’s framework represents a holistic model of Islamic pedagogy in which ethics and methodology are inseparable. In contemporary digital learning environments characterized by information overload and academic shortcuts, this framework offers a morally grounded and methodologically rigorous alternative capable of strengthening academic integrity and character formation among Generation Z learners.